Microstructure formation in dip-coated particulate films - Peukert, Wolfgang; Günther, Lübbe; Goerigk, Günter; Dingenouts, Nico (Journal of Colloid and Interface Science, 2006)
The microstructure-dependence of dip-coated particulate thin films on the stability of an aqueous silica sol used as coating bath is studied. Different stability conditions are adjusted in the sol by changing electrolyte concentration and pH value. Care was taken to avoid pronounced aggregation of the particles before the coating process. The characterization of the stability behavior gives clear evidence of a non-DLVO contribution at low pH values that is attributed to hydration forces. Structural evolution of the particulate network during film formation is studied using a dialysis accumulation procedure. The viscosity of the accumulated sol is measured as a function of shear rate and related to the drying characteristic of the coating process. Atomic force microscopy (AFM), small-angle X-ray scattering (SAXS) and N sorption are used to obtain information on the surface and volume structure of the dip-coated films. The structure of coatings is found to distinctly vary with stability parameters. This is attributed to changing interactions during the first drying stage. Finally, the influence of coating structures on the light transmission properties is determined. A comparison between the extinction of the uncoated and the coated substrate revealed a difference of up to ±50% in dependence on the microstructure. © 2005 Elsevier Inc. All rights reserved.
Keywords: Colloidal stability; Dip coating; Film structure; Particles; Pore size distribution; Rheology; Small-angle scattering